Antimicrobial compound extraction from spirulina (Asthrospira plantensis) using methanol, acetone, and diethyl ether as the solvent system. - Espinosa, Ma. Beatrice Y.
A new solvent system comprised of methanol, acetone, and diethyl ether combined in 5:2:1 ratio is used in extracting the antimicrobial compounds from the microalgae Arthrospiraplantensis, or commonly known as Spirulina. The cyanobacteria were cultured under laboratory conditions for 30 days to allow production of the antimicrobial metabolites. The solvent system was used for extraction after the time of culture and the crude extracts were tested against three bacteria - Escherichia coli ATCC 35818, Vibrio harveyi, and Staphylococcus aureus ATCC 275913. Four extract concentrations were prepared (25 percent, 50 percent, 75 percent, and 100 percent). Chloramphenicol was used as the positive control while the solvent system was used as the negative control. Antimicrobial assay was done using the paper disc diffusion method and the efficiency of the solvent was evaluated through the zones of inhibition of the targeted bacteria. The most sensetive to the cyanobacterial extract was Vibrio harveyi (15 mm) while Escherichia coli ATCC 35818 (8 mm) and Staphylococcus aureus ATCC 275913 (11 mm) were resistant. However all bacteria exhibited zones of inhibition and the 100 percent extract concentration yielded the widest zones.